To eliminate the variable \( x \) in the given system of equations, we need to manipulate the coefficients of \( x \) in such a way that they are opposites in the two equations.
Let’s look at the equations:
- Equation I: \( 5x + 3y = 19 \)
- Equation II: \( 2x - 4y = -8 \)
The coefficient of \( x \) in Equation I is \( 5 \) and in Equation II it is \( 2 \). To eliminate \( x \), we can make the coefficients equal and opposite.
One way to do this is to find a common multiple of \( 5 \) and \( 2 \). The least common multiple of \( 5 \) and \( 2 \) is \( 10 \). Therefore, we will try to make the coefficient of \( x \) in both equations equal to \( 10 \):
-
If we multiply Equation I by \( 2 \), we get: \[ 2(5x + 3y) = 2(19) \implies 10x + 6y = 38 \]
-
If we multiply Equation II by \( -5 \), we get: \[ -5(2x - 4y) = -5(-8) \implies -10x + 20y = 40 \]
Now, we have:
- \( 10x + 6y = 38 \)
- \( -10x + 20y = 40 \)
These two equations can now be combined to eliminate \( x \).
Therefore, the correct answer is option:
C. Multiply Equation I by 2 and multiply Equation II by negative 5.